COMPARISON OF HERBAL AND NON-HERBAL TOOTHPASTE TOWARDS REDUCTION OF PLAC INDEX IN ELEMENTARY SCHOOL CHILDREN, LAMPENERUT, ACEH BESAR REGENCY - Marzuki; Nuraskin, Cut Aja (Journal Dental Health, 2022)
Many Indonesian people suffer from dental and oral diseases. Based on riskesdas data in 2018, the criteria for children aged 5-9 years (67.3%) experienced problems in dental health while those who received treatment were only 14.6%, and the criteria for children aged 3-4 years (41.1%) had problems on dental health while those who received treatment were only 4.3%. Based on preliminary data on Lampeune State Elementary School children, according to Aceh Besar District, 7 of the 10 students examined were bad criteria and 3 of them were good criteria. Therefore, it is necessary to control the plaque index, controlling the plaque index can be done mechanically or chemically, mechanically by brushing teeth and using herbal toothpaste. The problem in this study is the comparison of herbal toothpaste with non-herbal toothpaste on the decrease in plaque index in children at the Lampeune State Elementary School, Aceh Besar District. The type of research used is a quasi-experimental research / guast experiment, using random sampling method with a population of 625 students and the number of samples used is 100 students on the criteria of age 7-12 years. From the results of the study, the average value of the decrease in plaque index after brushing teeth using herbal toothpaste was 1.486 while after using non-herbal toothpaste the plaque index score was 2.668. In this case, it means that there is a significant comparison between herbal toothpaste and non-herbal toothpaste, as evidenced by a p-value of less than 0.05, which is 0.000.